2014
DOI: 10.1002/eji.201344276
|View full text |Cite
|
Sign up to set email alerts
|

Functionally responsive self‐reactive B cells of low affinity express reduced levels of surface IgM

Abstract: SUMMARY Somatic gene rearrangement generates a diverse repertoire of B cells, including B cell receptors (BCR) possessing a range of affinities for self-Ag. Newly generated B cells express high and relatively uniform amounts of surface IgM (sIgM), while follicular (FO) B cells express sIgM at widely varying levels. It is plausible, therefore, that down-modulation of sIgM serves as a mechanism to maintain weakly self-reactive B cells in a responsive state by decreasing their avidity for self-Ag. We tested this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
(121 reference statements)
1
22
0
Order By: Relevance
“…An independent study came to similar conclusions by studying the functional properties of IgM LO and IgM HI Fo B cells in mice 81. An independent study came to similar conclusions by studying the functional properties of IgM LO and IgM HI Fo B cells in mice 81.…”
mentioning
confidence: 62%
“…An independent study came to similar conclusions by studying the functional properties of IgM LO and IgM HI Fo B cells in mice 81. An independent study came to similar conclusions by studying the functional properties of IgM LO and IgM HI Fo B cells in mice 81.…”
mentioning
confidence: 62%
“…Kirchenbaum et al (119) used a different approach to substantiate the hypothesis that dynamic downmodulation of surface IgM serves as a mechanism for maintaining weakly self-reactive B cells in a responsive state to foreign antigens by decreasing their avidity for self-antigen. They performed functional tests with IgM low and IgM high B cells from mice and showed that they mobilized Ca 2+ equivalently when the same number of IgM molecules were engaged.…”
Section: Beyond T Cells B Cell Tuningmentioning
confidence: 98%
“…The proportion of CD19+IgD+ B cells was lower in NSG- cmah -/- mice at 3 months and did not decline by 6 months as was found in NSG wt humanized mice. The proportion of CD19+IgM+IgD+ B cells in peripheral blood of both strains declined, and the proportion of CD19+IgM - IgD+ cells [32, 33] increased. We did not observe significant differences in the numbers of CD19+IgM+IgD - mature B cells between strains at 6 months (5.9 ± 0.9% and 7.7 ± 1.3% NSG- cmah -/- and NSG, respectively).…”
Section: Resultsmentioning
confidence: 99%